A metapoesia nos cadernos negros como afirmação da identidade negra e como forma de combate ao racismo - Grostein, Adele (2026)
The motivation for the development of this study arises from the observation of the recurrence of poems with metalinguistic themes in the poetic production of black authorship within contemporary brazilian literature. This research is based on the assumption that there is a reason that accounts for the large number of metapoems in black brazilian literature. Thus, this thesis seeks to investigate the function of metalinguage in the poetry produced by Samuel Neri, Cristiane Sobral, Bruno Gabiru, Catita, Cuti, Esmeralda Ribeiro, Benedita Lopes, Benício dos Santos Santos, Serafina Machado, and Fausto Antonio—contemporary black brazilian authors whose works address issues related to black identity and racism. Based on the definition of “metaliterature” proposed by Hélder Gomes (2010), this study formulates the hypothesis that the metalinguistic theme in Black Brazilian poetry published between 2012 and 2024 represents a way of presenting and defining for the reader a aesthetic that had long been rejected by readers and critics. In order to test this hypothesis, the research proposes an analysis of metalinguistic poems published in Cadernos negros over the last eight years. This thesis draws on reflections on metalinguage developed by Jakobson (1975) and Hutcheon (1984); on the ideas put forward in Literatura Negro-Brasileira (2010) by Cuti; and on Gabriel Nascimento’s reflections on linguistic racism (2019). The relevance of this research is justified by the scarcity of studies that specifically address metalinguistic themes in Black Brazilian literature, as well as by the need to study and disseminate a high-quality literary production that denounces and confronts racism through writing of a high aesthetic standard